The method of transmission matrix for investigating planar mechanisms - Sanh, Do; Khoa, Do Dang (Vietnam Journal of Mechanics, 2007)
In this paper the method of transmission matrix is applied for investigating planar mechanisms [5-7]. As is known, in many engineering problems, for example, in the problem of synthesis and analysis of motion, the following problem is more and more interested. There is an object (a particle or body) connected with a frame of reference, which moves with respect to another frame. It is necessary to define the configuration (the position, velocity, acceleration) of the object under consideration in the latter frame. There are two types of the frame of reference. A frame that is fixed in time named inertia frame or global frame of reference and the frame attached to each body of the system- the body frame of reference. The problem is stated now as follows: Determine the configuration in global frame of a particle fixed in any body of the system.In this paper a method is constructed for solving such a problem by means of transmission matrices.The obtained results are illustrated by examples.